LOCAL STRONGMAN KEMUKUS MOUNTAIN - Dyah Ayu Ambarwati (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
Kemukus mountain is one of the pilgrimage tourist attractions in the Sumberlawang sub-district, Sragen regency. Mount Kemukus has been famous for its prostitution activities under the guise of religious tourism. The paper is intended to see the strong man on the cubeb mountain. The method used is a qualitative descriptive approach with local strongman theory. Local Strongmen are local people who are successful in order to place them in the regional government to ensure that the allocation of resources to continue according to the main rules they want to be implemented must implement the main rules of the local government. The Local Strongman made efforts to protect the practice of prostitution by working with several regional officials. They also do various ways to make more money for their survival Keywords: Local Strongmen, Kemukus Mountain, Personal Interests